Study of Comparison of Salinity Value in Coastal of Sampang District Using Aqua Modis Satellite Image Data - S. Zainab; D. P. Solin (Nusantara Science and Technology Proceedings)
Salinity is one of the parameters that used for detecting the changes in ecosystems in shallow sea water. The high and low salinity will affect the lives of vegetation and animals. Identifying the salinity content of Sampang District is highly needed considering that Sampang District is well-known producer and exporter of salt. This study was emphasized in mapping the salinity value by using remote sensing algorithms. The mathematic models that used in this research are linear, exponential, logarithm, and power models. The result of this research shows that mapping by using level-2 aqua satellite image is well applied. The result shows that using wavelength 443 mm and 531 mm of Aqua Modis data presents the highest correlation values. The optimum regression for these two wavelength are Sal(ppt)=8,15*ln(Rrs_443)+66,128 with the value R2 as 0,8736 and Sal(ppt)= 8,15 *ln(Rrs_443) + 64,611 with the correlation value R2 as 0,8322. From these result, it can be concluded that there are no significant differences satellite image data for salinity to the data acquisition time.